The Influence of YouTube Social Media on Bhikku Dhirapunno's Personal Branding (#LogIndiCloseTheDoor on YouTube Chanel Deddy Corbuzier) - Rina Manggalani; Wistina Seneru; Widiyanto; Edi Sumarwan; Candra Kusuma (LPPM STIAB JINARAKKHITA LAMPUNG, 2023)
This research aims to determine the formation of personal branding through YouTube social media. YouTube plays an important role in building one's personal branding. This research uses an ex-post facto quantitative approach (non-experimental research) with a survey method. The population studied was viewers of the Log In Close The Door Bhikku Dhirapunno podcast on Deddy Corbuzier's YouTube channel. Based on the results of research and discussion regarding the influence of YouTube social media on Bhikku Dhirapunno's personal branding, it can be concluded that there is a significant influence of YouTube social media on Bhikku Dhirapunno's personal branding. The great influence of YouTube social media on Bhikku Dhirapunno's personal branding can be seen from the R square of 17.7%.